Life Satisfaction of Voluntarily Childfree Individuals in Indonesia - Gitta Azalia Budiyati; Sofia Tri Putri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Most of the childfree research remains focused on Western contexts, so studies in collectivist and pronatalist societies, such as Indonesia, remain limited. This study aims to explore the experiences and life satisfaction of childfree individuals in Indonesia. This study seeks to expand the literature by examining how childfree individuals interpret life satisfaction amid social norms that emphasize the importance of having children. This study uses a phenomenological qualitative approach, conducting in-depth interviews with five participants and employing thematic analysis to uncover the life experiences of childfree individuals in Indonesia. The findings suggest that the decision not to have children affects participants' life satisfaction, and that the presence of children negatively affects their lives. The domains of life satisfaction identified in this study were relationships with partners, finances, and leisure time. Freedom in careers, hobbies, and activities contributes to participants' life satisfaction. These findings provide an alternative perspective on pronatal assumptions that link the existence of children to family happiness and offer implications for counseling practices when accompanying childfree individuals living in societies with strong pronatal values. Keywords: childfree, good health and well-being, life satisfaction, phenomenology